Item Analysis of an Early Social Responsiveness Scale for Assessing Autism Risk - Chloe Boynton; Opal Ousley; Reina S. Factor (Behavioral Sciences)
Early diagnosis of autism spectrum disorder (ASD) is vital for effective intervention and improves social and behavioral development. The previous literature has shown that the Early Social Responsiveness (ESR) assessment is effective at detecting ASD risk in individuals as early as 13 months of age (“parent study”). However, an item analysis that examines individual item scores has not been conducted to further elucidate the strength of this assessment. In this study, we analyzed an existing dataset (collected in the parent study) containing individual item responses from the ESR assessment of 120 children (n = 61 males and n = 59 females; age range = 15–24 months). Through item analysis, we determined which ESR items or item sets are best at differentiating ASD risk from non-ASD risk. Ease of social engagement (i.e., questions assessing the administrator’s perceived level of effort in engaging the child) was the most effective risk indicator, with the hat and tickle activities being least effective at indicating ASD risk. These results could contribute to optimizing the scale and facilitating its clinical adoption.